2012
DOI: 10.1016/j.juro.2011.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery After Partial Nephrectomy: Effects of Volume Loss and Ischemic Injury

Abstract: In this cohort volume loss and not ischemia time was the primary determinant of ultimate renal function after partial nephrectomy. Technical modifications aimed at minimizing volume loss during partial nephrectomy while still achieving negative margins may result in improved functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(129 citation statements)
references
References 16 publications
8
112
2
Order By: Relevance
“…Our study also supports the findings by the group in Cleveland Clinic of the impact of parenchymal volume preservation on renal function after partial nephrectomy for small renal masses. 21,22 This impact may be even more important than warm ischemic time. Interestingly, kidney volumes obtained in these studies were larger in the Western population (median of 184-219 mL) than those in the Asian population 14,20 and may be related to body size.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also supports the findings by the group in Cleveland Clinic of the impact of parenchymal volume preservation on renal function after partial nephrectomy for small renal masses. 21,22 This impact may be even more important than warm ischemic time. Interestingly, kidney volumes obtained in these studies were larger in the Western population (median of 184-219 mL) than those in the Asian population 14,20 and may be related to body size.…”
Section: Discussionmentioning
confidence: 99%
“…15 The median WIT for simple tumors was 15 (IQR 9) minutes, which is within the safe range of <25 minutes described by Thompson and associates. 20 Although a growing body of evidence suggests that the amount of renal parenchyma removed rather than WIT is the determinant of final degree renal function preservation, 21,22 long WIT, especially in the setting of preexisting renal impairment and solitary kidney, is an important modifiable factor. [23][24][25][26] The rates of intraoperative (3.3%) and postoperative complications (30%) are slightly higher than in some of the published RAPN series, 27 but they are comparable with results from other OPN series for solitary kidneys.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Simmons et al suggested that a decrease of GFR in PN surgery may be influenced by 3 factors: functional volume loss, ischemia related acute kidney injury and mechanical trauma effects [14]. Collateral damage due to renorrhaphy volume loss occurs mainly as a result of resected normal parenchyma adjacent to the tumor margin.…”
Section: Discussionmentioning
confidence: 99%